2008
DOI: 10.1103/physreve.77.031913
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of binding free energy for adsorption of antimicrobial peptide lactoferricin B on a POPC membrane

Abstract: Molecular dynamics (MD) simulations are used to study the interaction of a zwitterionic palmitoyl-oleoyl-phosphatidylcholine (POPC) bilayer with the cationic antimicrobial peptide bovine lactoferricin (LFCinB) in a 100 mM NaCl solution at 310 K. The interaction of LFCinB with POPC is used as a model system for studying the details of membrane-peptide interactions, with the peptide selected because of its antimicrobial nature. Seventy-two 3 ns MD simulations, with six orientations of LFCinB at 12 different dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 23 publications
1
44
0
Order By: Relevance
“…3)" rend="display" xml:id="FD3">K=1false(l-lfalse)llitalicdze-w(z)/kBT, where w ( z ) = 0 is assumed for the unbound macrostate as described in detail by (Vivcharuk et al, 2008). The integral over the bound macrostate goes from l′ = 30 Å to l = 51 Å.…”
Section: Methodsmentioning
confidence: 99%
“…3)" rend="display" xml:id="FD3">K=1false(l-lfalse)llitalicdze-w(z)/kBT, where w ( z ) = 0 is assumed for the unbound macrostate as described in detail by (Vivcharuk et al, 2008). The integral over the bound macrostate goes from l′ = 30 Å to l = 51 Å.…”
Section: Methodsmentioning
confidence: 99%
“…In 29 and15 the position, PMF, W ( z ), was evaluated from the orientational PMF, W ( z ,Ω), where Ω is the vector of rotational degrees of freedom. It was found that the orientational PMF, has no strong dependence on the rotation around space-fixed axes y with the origin at the peptide center of mass.…”
Section: Methodsmentioning
confidence: 99%
“…To find the PMF, W ( D ), from the simulation, we apply the force method which was developed for the PMF calculation of a peptide in the vicinity of a neutral POPC membrane 29 and charged POPG membrane; 15 it is a variant of constrained MD and thermodynamic integration. 30–35 More specifically, we use the relation F̄ ( D ) = −∂ W ( D )/∂ D , where F̄ ( D ) is the mean force (which is in z -direction by symmetry) on the peptide for fixed D .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 However, for the simulation to make any kind of prediction, an accurate structure of the lipids making up the membrane is needed. When such a structure is not available, as is usually the case, the atomÀatom potential interaction parameters producing the inputted lipid structure can be "tweaked" to improve the fit between simulated and experimental data.…”
Section: ' Introductionmentioning
confidence: 99%